1989
DOI: 10.1093/infdis/159.3.472
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibody Responses to Epstein-Barr Virus in HIV-Infected Homosexual Men

Abstract: We investigated the association between human immunodeficiency virus (HIV) and Epstein-Barr virus (EBV) infections in 593 homosexual men. The status of EBV infection in this group was evaluated based on serological evidence of EBV-specific antibody responses. The geometric mean titers (GMT) of antibody to EBV capsid antigen (EBV-VCA) (1:154) and EBV early antigen (EA) (1:16) in 141 HIV-seropositive men were significantly higher than respective titers in 452 HIV seronegative men (1:95 and 1:12). Antibody titers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…Possible reasons for the predominant CTL activity to gH during HIV-1 infection include cross-reactivity to non-HHV-8 antigens, such as the EBV homologue of gH. Indeed, EBV infection is active in a large proportion of HIV-1-infected individuals, as shown by persistent shedding of the virus and high titers of antibodies to EBV [12,13]. However, this is unlikely to be the cause of the anti-HHV-8 CTL activity detected in our study, because we have shown in longitudinal studies that CD8 ϩ T cell responses to these HHV-8 lytic proteins are not due to cross-recognition by T cells Alternatively, this more robust anti-gH T cell reactivity could be related to selective production or more dominant immunogenicity of this lytic protein during persistent HIV-1 infection, with consequent differential T cell reactivity that is suppressed at higher HIV-1 loads.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for the predominant CTL activity to gH during HIV-1 infection include cross-reactivity to non-HHV-8 antigens, such as the EBV homologue of gH. Indeed, EBV infection is active in a large proportion of HIV-1-infected individuals, as shown by persistent shedding of the virus and high titers of antibodies to EBV [12,13]. However, this is unlikely to be the cause of the anti-HHV-8 CTL activity detected in our study, because we have shown in longitudinal studies that CD8 ϩ T cell responses to these HHV-8 lytic proteins are not due to cross-recognition by T cells Alternatively, this more robust anti-gH T cell reactivity could be related to selective production or more dominant immunogenicity of this lytic protein during persistent HIV-1 infection, with consequent differential T cell reactivity that is suppressed at higher HIV-1 loads.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased IgA responses after seroconversion may be part of HIV-related B cell changes and thus should be interpreted with caution. Activation of both EBV and CMV following HIV infection has already been noted by others and may be due to both direct effects (Lai, Li & Volsky, 1989) and to the HIVrelated profound defect in cellular immunity which is important in controlling latent herpes virus infections (Birx, Redfield & Tosato, 1986;Rahman et al, 1989;Rinaldo, 1990). There is strong experimental evidence (Gendelman et al, 1986;Pagano et al, 1988;Skolnik et al, 1988;Albrecht et al, 1989;Clouse et al, 1989) and some clinical observations suggesting that activated EBV or CMV infections may be associated with enhanced replication of pre-existing HIV and accelerated progression to AIDS, but this cannot be inferred from our series.…”
Section: Discussionmentioning
confidence: 77%
“…This could be the result of specific cell-to-cell interactions enhanced by the in vitro conditions. It is a well-known fact that HIV-infected people have a uniformly deftcient virus-specific cytotoxic lymphocyte function, and specifically present serious impairment in T-cell suppression of EBV-infected B-cells (5); in consequence, the number of circulating infected lymphocytes is abnormally high in these individuals (6,12). Therefore, there is an increased probability that a progressive proliferation of these cells occurs when cultured in vitro.…”
Section: Discussionmentioning
confidence: 99%